A comparative study of porous polyethylene versus absorbable polydextro- and polylevolactic-lactide plate in reconstruction of isolated medial orbital wall fracture. Issue 2 (February 2022) - Cha, Han Gyu; Nam, Seung Min; Kim, Yong Bae; Park, Eun Soo; Choi, Chang Yong
Summary: Background: Several materials for medial orbital wall reconstruction have been mentioned in the literature. Our main purpose was to investigate postoperative enophthalmos and diplopia after medial orbital wall reconstruction with polydextro- and polylevolactic (poly-L /DL ) acid (P[L /DL ]LA) mesh plates and porous polyethylene plates. Methods: Using a retrospective study design, we enrolled a cohort of isolated medial blowout fracture patients treated during a 58-month interval. The predictor variable was medial orbital wall reconstruction materials (P(L /DL )LA mesh plate and porous polyethylene plate. The main outcome variables included the occurrence of postoperative enophthalmos and diplopia at 1 week, 1, 3, 6, and 12 months post-surgery. Appropriate descriptive, uni- and bivariate statistics were computed, and P < 0.05 was considered significant. Results: Three hundred-two isolated medial blowout fracture patients were included (24.5% females, 67% treated with P(L /DL )LA mesh plate). Exophthalmos measured highest in both groups 1 week after surgery and decreased steadily for 6 months postoperatively. Statistically significant differences were observed between both groups at 1 week, 1 month, and 3 months after surgery, with a higher incidence of exophthalmos observed in the P(L /DL )LA mesh plate group ( P < 0.001). No significant differences were observed at 6 and 12 months after surgery. Conclusion: The occurrence of enophthalmos after medial blowout fracture reconstruction with P(L /DL )LA mesh plate is comparable with the use of porous polyethylene plate. Both P(L /DL )LA mesh and porous polyethylene plates are, therefore, reliable implants for medial orbital wall reconstruction.